Hubungan antara Usia Menarke dengan Tinggi Badan dan Panjang Kaki Saat Dewasa - Hapsari, Anindita Putri; Wiryanto, Tri Budi; Sumardiyono, . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Menarche happens when estrogen activity at the peak, that is showed with high level estrogen. In other words, age at menarche is the first onset of high level estrogen. Estrogen not just has important role in reproduction system but also in bone growth. Low level estrogen, or estrogen level when estrogen activity has not at peak yet during puberty time, can stimulate bone growth with growth hormone stimulation mechanism while high level estrogen, or estrogen level when estrogen activity at the peak, can accelerate the closure of epiphysial growth disks so the bone growth will stop in stages. Based on that theory, there is correlation between age at menarche with adult height and leg length. But there are still pros and cons about the result of correlation between age at menarche with final height and leg length from researchers in different places. Therefore, research about age at menarche in relation with adult height and leg length is needed. Methods: This research is analytic observational â cross sectional. The data about age at menarche, height and leg length is gained from interview and measurement with 60 medical students of Sebelas Maret University. The data gained from the research is analyzed statistically using t test and Pearson Correlation test. Results: The average of age at menarche is 12.42 years old. In t test, there is no significant average difference of height (p = 0.612) and leg length (p = 0.341) between later age at menarche (higher than the average) group with early age at menarche (lower than the average) group. In Pearson Correlation test, there is no correlation between age at menarche with adult height (p = 0.985) and leg length (p = 0.443). Conclusions: In conclusion, there is no correlation between age at menarche with adult height and leg length. Keywords: age at menarche, height, leg lengthÂ